Should Undergraduate Lectures be Compulsory? The Views of Dental and Medical Students from a UK University - Alaa Daud; Aaron Bagria; Kushal Shah; James Puryer (MDPI AG, 2017)
Formal lectures have been a traditional part of medical and dental education, but there is debate as to their compulsory status. This study was designed to explore dental and medical students' views on compulsory lectures and the use of Video-Recorded Lectures (VRL). A cross-sectional study of University of Bristol students in Years 2 to 4 was conducted using an online questionnaire. The majority of both dental (76%) and medical (66%) students felt lectures should be non-compulsory. The most common learning resources used by both dental and medical students were live lectures, lecture handouts and VRL. The majority of both dental (84%) and medical (88%) students used VRL. Most students attended lectures all of the time both before and after the introduction of VRL, even though most dental and medical students believe lectures should be non-compulsory. VRL is a popular learning resource. These findings tie-in with General Dental Council and General Medical Council recommendations that encourage self-directed learning. Dental and Medical schools should offer a range of learning resources and make use of current technology, including the use of VRL.